Обеспечение устойчивости вентильного электродвигателя конверсионного гибридного автомобиля - Двадненко, В. Я. (НТУ "ХПИ", 2014)
Рассмотрены особенности применения тягового вентильного электродвигателя на основе генераторной синхронной электрической машины для конверсии обычного автомобиля в подзаряжаемый гибридный автомобиль. Предложена методика обеспечения устойчивости такого электродвигателя с помощью электронного управления компенсацией реакции якоря. Разработан и практически реализован на основе разработанной методики блок управления возбуждением вентильного электродвигателя на основе автомобильного генератора Г290.

Conversion of a conventional car into a Plug-in hybrid reduces fuel consumption and makes the car environmentally friendly. To make this conversion was economically attractive, it is necessary to make a suitable inexpensive electric motor. This engine can be BLDC motor based on a powerful automotive generator. The article has been considered the stability of the traction BLDC motor. A method for ensuring the sustainability of such a motor by means of electronic compensation control of armature reaction. Developed and practically implemented BLDC motor on the basis of the developed method. This motor is designed based on the powerful automobile generator G290. Proposed a scheme for the control unit voltage excitation, which provides stable operation BLDC motor. The proposed methodology and its implementation of the circuit tested in practice in the conversion of Plug-in hybrid car «Lanos pickup». Test results confirmed the effectiveness of the technical solution.
Stability BLDC motor of conversion hybrid car
Keywords: компенсация реакции якоря; электропривод; автомобильный генератор; пробег; BLDC motor; vehicle conversion; Plug-in hybrid car